The re-coding of rural development rationality: tracing EU Governmentality and Europeanisation at the local level - Sune Wiingaard Stoustrup (European Planning Studies, 2021)
The evolution of EU rural development policies and imaginaries have entailed that rural areas in Europe and their residents have been assigned specific roles concerning local responsibility and identities when it comes to attaining positive territorial development. The paper approaches the rationality of rural development as community-led through a lens of Governmentality and Europeanisation to explore how the local alignment of actions and government rationalities are linked. The presented research outlines rural development discourse first in EU rural policy and then at the local level through an analysis of text data published by a local development association. The paper traces the linkage between the two institutional levels and establishes how the success of rural development is not only to constitute issues and themes in a particular form but also to have these embedded locally.
Keywords: 710; Governmentality; Europeanisation; spatial planning; rural development